Chaplain Documentation and the Electronic Medical Record: A Survey of ACPE Residency Programs. Issue 2 (2nd April 2016) - Tartaglia, Alexander; Dodd-McCue, Diane; Ford, Timothy; Demm, Charles; Hassell, Alma
Abstract : This study explores the extent to which chaplaincy departments at ACPE-accredited residency programs make use of the electronic medical record (EMR) for documentation and training. Survey data solicited from 219 programs with a 45% response rate and interview findings from 11 centers demonstrate a high level of usage of the EMR as well as an expectation that CPE residents document each patient/family encounter. Centers provided considerable initial training, but less ongoing monitoring of chaplain documentation. Centers used multiple sources to develop documentation tools for the EMR. One center was verified as having created the spiritual assessment component of the documentation tool from a peer reviewed published model. Interviews found intermittent use of the student chart notes for educational purposes. One center verified a structured manner of monitoring chart notes as a performance improvement activity. Findings suggested potential for the development of a standard documentation tool for chaplain charting and training.